Exploring the contribution of the lyric completion songwriting technique to a music therapy assessment session with preadolescent children in a children's home - Lotter, Carol Barbara (University of Pretoria, 2023)
Mini Dissertation (MMus (Music Therapy))--University of Pretoria, 2022.